EVALUATION OF THE EXISTENCE OF OTHER LAWS AND REGULATIONS FROM THE PERSPECTIVE OF LEGISLATIVE SCIENCE - Insan Tajali Nur; Aullia Vivi Yulianingrum; Setiyo Utomo Utomo (Faculty of Law, Universitas Pekalongan, 2025)
This article is to analyze the existence of other laws and regulations listed in Article 8 of Law Number 12 of 2011 concerning the Formation of Laws and Regulations; which is assumed to be regulation . The current condition is that the legal product in question is in its formation it is very easy and fast to handle state affairs. However, the scope and testing are not yet clear. and the amount is uncontrolled. The main problem of this research; First , in the form of the need to evaluate the characteristics of the legal product contained in Article 8 in the a quo provisions . Second , tracing position law or degree of other laws and regulations with regulation legislation is seen from the perspective of legal science. The method used is classified as normative legal research with a legal and doctrinal approach. Thus, the results of this study explain several important things, namely First , there were findings in the form of differences characteristics between statutory regulations (regeling) and legislative regulations other (policy regulations) or called as a Regulation Policy. The difference in legal status can be measured through several indicators such as the formation, scope or nature and its testing. Both sit down regulation legislation other as regulation implementer to synergize regulations and policies through separation of the position of other laws and regulations to be included in laws which are per se related to government administration with touchstone of General Principles of Good Governance through Administrative Justice